2004
DOI: 10.1007/s00114-004-0545-5
|View full text |Cite
|
Sign up to set email alerts
|

Communal nesting and kinship in degus (Octodon degus)

Abstract: Communal nesting is a fundamental component of many animal societies. Because the fitness consequences of this behavior vary with the relatedness among nest mates, understanding the kin structure of communally nesting groups is critical to understanding why such groups form. Observations of captive degus (Octodon degus) indicate that multiple females nest together, even when supplied with several nest boxes. To determine whether free-living degus also engage in communal nesting, we used radiotelemetry to monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
182
2
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(190 citation statements)
references
References 18 publications
4
182
2
2
Order By: Relevance
“…Some rodent species that are diurnal in the field become nocturnal under certain laboratory conditions, including degus (Ebensperger et al, 2004;Kas and Edgar, 1999), hamsters (Gattermann et al, 2008), tuco-tucos (Tomotani et al, 2012), cururos (Urrejola et al, 2005), Nile grass rats (Blanchong et al, 1999) and golden spiny mice (Cohen et al, 2010). These discrepancies in circadian rhythms between the laboratory and field raise the question of whether a 'default' circadian phenotype actually exists.…”
Section: Homeostatic Feedback On Peripheral Circadian Phasementioning
confidence: 99%
“…Some rodent species that are diurnal in the field become nocturnal under certain laboratory conditions, including degus (Ebensperger et al, 2004;Kas and Edgar, 1999), hamsters (Gattermann et al, 2008), tuco-tucos (Tomotani et al, 2012), cururos (Urrejola et al, 2005), Nile grass rats (Blanchong et al, 1999) and golden spiny mice (Cohen et al, 2010). These discrepancies in circadian rhythms between the laboratory and field raise the question of whether a 'default' circadian phenotype actually exists.…”
Section: Homeostatic Feedback On Peripheral Circadian Phasementioning
confidence: 99%
“…degus live in relatively large groups ranging from 1 to 12 adult individuals , and females of this species exhibit communal care of offspring [Ebensperger et al, 2004]. These characteristics have been documented in at least four populations of this species [Ebensperger et al, 2004[Ebensperger et al, , 2012Jesseau, 2004;Sobrero et al, unpubl. data], implying a high frequency of social interactions and probably a need for cognitive skills underlying these interactions.…”
Section: Model Species and Hypothesis Predictionsmentioning
confidence: 99%
“…The original research reported herein was performed under guidelines established by the Pontificia Universidad Católica de Chile Bioethical Committee (CBB-042/2011) and adhered to Chilean laws [permits 1-154.2010 (7989), 1-109.2011 (6749), 1-90.2011 (4731) and 1-95-2012 (4486) [Ebensperger et al, 2004[Ebensperger et al, , 2012, we placed traps near burrow openings and inside patches with high shrub cover and baited them with rolled oats, fruity cereals and sunflower seeds. During each capture, we recorded sex, body mass (to 0.1 g) and reproductive status (whether a female had a perforated vagina, was pregnant or lactating) of all degus, and each animal was marked with an ear tag (Monel 1005-1; National Band and Tag Co., Newport, Ky., USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations